Teletandem and Intercomprehension - LEONE, Paola (The ESPecialist, 2022)
Teletandem is implemented in several universities, and different learning scenarios are designed for meeting the manifold needs of a changing society. Intercompréhension Orale et Teletandem (IOTT), a telecollaboration project developed by University of Lyon 2 and University of Salento, responds to this challenge by aiming to develop the receptive, productive, and interactive skills required when communicating with a speaker/writer of a different but related language to one’s own (e.g., speakers of Spanish and French: romance languages). IOTT also develops theoretical knowledge and metacommunicative skills necessary to highlight and analyse strategies for solving communication problems - that is, how concepts and meanings can be mediated. This is accomplished using a macrotask named MINTT, i.e., a sequence of tasks promoting students’ reflectivity, encouraging a propensity for formative critical thinking. After discussing the notion of Intercomprehension, IOTT learning design is described, highlighting areas of potential learning of this Teletandem-based Learning Scenario. Video recordings of Teletandem Oral Sessions and learner diaries, written by students after each session, are mentioned to show how students perceive such a challenging experience, how they resolve communication problems during Teletandem Oral Sessions and how they analyse processes of meaning negotiation.